Tunable magnon-photon coupling in a compensating ferrimagnet - from weak to strong coupling - Maier-Flaig, H.; Harder, Michael; Klingler, S.; Qiu, Zhiyong; Saitoh, Eiji; Weiler, Mathias; Gepraegs, S.; Gross, Rudolf; Goennenwein, S. T. B.; Huebl, Hans (Applied Physics Letters, 2017)
We experimentally study the magnon-photon coupling in a system consisting of a compensating ferrimagnet gadolinium iron garnet (GdIG) and a three-dimensional microwave cavity. The temperature is varied in order to tune the GdIG magnetization and to observe the transition from the weak coupling regime to the strong coupling regime. By measuring and modelling the complex reflection parameter of the system, the effective coupling rate geff and the magnetization Meff of the sample are extracted. Comparing geff with the magnon and the cavity decay rate, we conclude that the strong coupling regime is easily accessible using GdIG. We show that the effective coupling strength follows the predicted square root dependence on the magnetization.
CRIS-Team Scopus Importer:2023-03-27